Assisted Community Housing Initiative in Dhaka: Rethinking Role of NGOs in Affordable Housing Development. (September 2018) - Begum, Halima; Heywood, Philip Richard; Susilawati, Connie
This research highlights how the strength of a group of mobilized slum dwellers was harnessed to bring in change in their housing condition. The community, with active support from a non-government organization, was able to develop housing for themselves. The article demonstrates that assisted community housing as an approach is capable of offering a sustainable housing development solution in a resource-constrained country like Bangladesh. The article aims at examining the context and the process, and identifying the operational barriers, and it explores future prospect of this approach in a specific context. Through elaborating on the community efforts, the article sheds lights on the difficulties that were encountered by the NGO and the community, making this a shared struggling experience. It identifies that with a few policy-level interventions and changes in operational practices of different government agencies, a supportive environment can be created which will foster NGO's stewardship to making this approach produce more equitable, efficient, affordable and, above all, sustainable housing development for the urban poor.